Walk this underground world - Baker, Kate,Brewster, Sam (Big Picture Press, 2019)
Take a journey around the globe and explore some of the curious worlds hidden beneath our feet. From prairie dog towns and ant cities to shopping malls and treasure-filled tombs, there are new surprises to discover on every page
On card pages with more than 80 flaps to lift
Keywords: Bilderbuch; Sachbilderbuch; Civilization; Subterranean / Juvenile fiction; Underground areas / Juvenile fiction; Burrowing animals / Juvenile fiction; Burrowing animals; Civilization; Subterranean; Underground areas; Fiction; Juvenile works; Lift-the-flap books; Picture books; Stories in rhyme; Untergrundbahn; Höhlentiere; Unterirdische Welt